Post-Contract Cost Control for Building Construction Projects - Chin Keng, Tan (Journal of Technology Management and Business, 2024)
Cost control is implemented to manage the cost of construction projects. Cost control is important in both pre-contract and post-contract stage but it is more vital in the latter stage. It is a continuous process and must be conducted throughout the project to ensure the final construction cost does not exceed the estimated cost and thus preventing cost overrun. Various factors may lead to cost overrun especially in building construction projects. Inadequate cost management is not a matter to be taken lightly because it results in a large number of cost overrun. This alarming problem is not only negatively affecting the parties involved in the project but also the nation. Hence, this study is carried out with the aim to mitigate cost overrun by practicing effective cost control. This research is conducted to identify the post-contract cost control practices implemented by contractors for building construction projects, the challenges encountered and the strategies to overcome the challenges. The method utilized is the quantitative method which is conducting questionnaire survey. 28 respondents from G6 and G7 contractors have provided feedbacks and the results obtained are analyzed by using Statistical Social Package Science (SPSS). For the first objective, the post-contract cost control practices for building construction projects include monitoring material cost, using bill of quantities to manage construction cost, monitoring overheads, monitoring labour cost and interim valuations. For the second objective, the challenges encountered include poor project planning, poor communication between project parties, improper contract documentation and unpredictable construction work environment. For the last objective, the strategies to overcome the challenges include good construction planning, effective site supervision, appointment of qualified management staff, good co-ordination between project team members, clear understanding of the project scope, effective contract administration, effective site management, clear process of the project control and use of appropriate construction methods.